Judge's Considerations in Law Enforcement in the Case of Intermediary in Illicit Drug Trafficking with Alternative Charges (Analysis of Decision Number: 500/PID. SUS/2024/PN.PLG) - Gading Radevi; Hambali Yusuf; Erli Salia (Utan Kayu Publishing, 2025)
The problem of narcotics in Indonesia is currently a challenge for all levels of society, not only for law enforcers in terms of the police to prevent drug abuse but also a challenge for all parents in Indonesia so that their children are not involved in drug abuse, because the number of drug abuse in Indonesia always increases from year to year, as in decision Number 500 / Pid.Sus / 2024 / PN Plg. So the problem is what are the judge's considerations in passing his verdict using alternative charges against drug intermediaries in verdict Number 500/Pid.Sus/2024/PN Plg? Then what are the sanctions against drug intermediaries in Law Number 35 of 2009 concerning Narcotics? The method used is the normative legal research method using primary and secondary legal materials. Meanwhile, the results of the study explain the Judge's Considerations in Passing His Verdict Using Alternative Charges Against Drug Intermediaries in Decision Number 500/Pid.Sus/2024/PN Plg, namely considerations from the legal aspect and considerations from the non-legal aspect so that the judge's considerations are considerations from the evidence and considerations of the elements of narcotics crimes regulated in Law Number 35 of 2009 concerning Narcotics. And the sanctions against drug intermediaries in Law Number 35 of 2009 concerning Narcotics, the sanctions for intermediaries in this law are the same as the sanctions for distributors, thus the defendant P was sentenced to 8 (eight) years in prison and a fine of Rp 1,000,000,000.00 (one billion rupiahs), if the fine is not paid, it will be replaced with imprisonment for 6 (six) months. And sentenced the defendant to pay court costs of Rp 5,000, - (five thousand rupiahs).